(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The Avian influenza (AI) is aspreadableinfection of the birds and humans affected by type A of influenza virus. Highly pathogenic avian influenza (HPAI) caused by the viruses subtype (H5N1) and (H5N8) is consider as a definite risk to the poultry industry and human health and it is started as the occasional revolutionize a satisfactory because of migratory bird which consider as a carrier of the disease. Twenty oropharyngeal swabs were collected from infected flock have suffer from sudden death with high mortality, all these samples were collected from (1-5) days after clinical signs appears and the results summarized by three farms infected with HPAI subtype (H5N8), three viral isolates strain out of 20 samples were identified by RT-PCR assay, two of them have layer origin while one have broiler origin, the three sequencing results in this study have been presented to the gene bank database under accession number MN689674.1 and MN658854.1, phylogenetic analysis of our sequences were used to relatedness of strain obtaining with other avian influenza viruses around the world, the a current sequences of avian H5N8 strains were found to be related as a common ancestor with Iranian registered strain.